Impact of increasing dose of intracoronary adenosine on peak hyperemia duration during fractional flow reserve assessment. (1st June 2019) - Verdoia, Monica; Erbetta, Riccardo; Sagazio, Emanuele; Barbieri, Lucia; Negro, Federica; Suryapranata, Harry; Kedhi, Elvin; De Luca, Giuseppe; ,
Abstract: Background: Fractional Flow Reserve (FFR) is currently indicated as a first line strategy for the functional assessment of intermediate coronary stenoses. However, the protocol for inducing hyperemia still lacks standardization. Intracoronary adenosine boli, with a progressive increase to high-dosage, have been proposed as a sensitive and accurate strategy for the classification of coronary stenoses, although being potentially affected by the achievement of plateau of the effect and by a less prolonged and stable hyperemia as compared to intravenous administration. Therefore, the aim of the present study was to define the conditioning parameters and assess the impact of increasing-dose intracoronary adenosine on peak hyperemia duration in patients undergoing FFR for intermediate coronary stenoses. Methods: FFR was assessed in patients with intermediate (40 to 70%) lesions by pressure-recording guidewire (Prime Wire, Volcano), after induction of hyperemia with intracoronary boli of adenosine (from 60 to 1440 μg, with dose doubling at each step). Hyperemic duration was defined as the time for the variation form minimum FFR ± 0.02 and time to recovery till baseline values. Results: We included 87 patients, undergoing FFR evaluation of 101 lesions. Mean peak hyperemia duration and time to recovery significantly increased with adenosine doses escalation ( p  = 0.02 and p  < 0.001). Peak hyperemia duration and time to recovery with 1440 μg adenosine were 14.5 ± 12.6 s and 45.2 ± 30.7 s, respectively. Hyperemia duration was not related to Quantitative Coronary Angiography (QCA) parameters or FFR values. In fact, a similar increase in the time of hyperemic peak was noted when comparing patients with positive or negative FFR (pbetween  = 0.87) or patients with lesions < or ≥20 mm (pbetween  = 0.92) and lesions involving left main coronary or proximal left anterior descending artery (LAD) (pbetween  = 0.07). A linear relationship was observed between time to recovery and FFR variations, with a greater time to baseline required in patients with FFR ≤ 0.80 ( p  = 0.003) and in lesions ≥ 20 mm ( p  = 0.006), but not in LAD/LM lesions ( p  = 0.55). Conclusions: The present study shows a progressive raise in the duration of peak hyperemia and time to recovery, after the administration of increasing doses of intracoronary adenosine for the assessment of FFR. Therefore, considering the potential advantages of a high-dose adenosine protocol, allowing a more prolonged hyperemia and a more precise and reliable measurement of FFR, further larger studies with such FFR strategy should certainly be advocated to confirm its safety and benefits, before its routinely use recommendation. Highlights: Hyperemic protocol for Fractional Flow Reserve (FFR) assessment is still debated In 101 intermediate stenoses undergoing FFR adenosine doses escalation increased mean hyperemia duration and time to recovery Peak hyperemia duration was not related to Quantitative Coronary Angiography (QCA) parameters or FFR values. Total hyperemia (time to recovery) was greater for FFR<0.80 and in lesions ≥ 20mm High-dose adenosine should be preferred for more reliable measurement of FFR